2013
DOI: 10.1159/000351116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tiotropium and Salmeterol/Fluticasone Propionate on Airway Wall Thickness in Chronic Obstructive Pulmonary Disease

Abstract: Background: Triple inhalation therapy with tiotropium (Tio) and salmeterol/fluticasone propionate combination (SFC) is widely used in the treatment of chronic obstructive pulmonary disease (COPD). However, the effects of triple therapy on airway structural changes remain unknown. Objective: The aim of the study was to assess the effects of Tio, salmeterol (SM), SFC and Tio plus SFC on airway dimensions in COPD. Methods: A randomized, open-label, 4-way study (n = 60) was conducted comparing 16-week treatment pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Treatment of both diseases includes inhaled corticosteroids (ICS) [1]. ICS have been extensively studied for the treatment of COPD patients with frequent exacerbations, demonstrating a reduction of acute exacerbations [2] and an improvement in pulmonary function [3], and they are a mainstay of treatment for patients with asthma [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment of both diseases includes inhaled corticosteroids (ICS) [1]. ICS have been extensively studied for the treatment of COPD patients with frequent exacerbations, demonstrating a reduction of acute exacerbations [2] and an improvement in pulmonary function [3], and they are a mainstay of treatment for patients with asthma [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have shown that CT indices that quantify airway wall thickening and the presence and severity of emphysema are correlated with pulmonary function measurements [13e15,17]. Recently, we have shown that triple inhalation therapy of tiotropium and Advair ® reduces airway wall thickness and pulmonary hyperinflation than monotherapy [18].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Our proprietary software for 3D-CT has the ability to assess Ai in 3 rd to 6 th generation airways 10,12, 13,18,19 , and furthermore the dual screen system enables us to simultaneously compare identical sites using two sets of CT data.…”
Section: Introductionmentioning
confidence: 99%